Determining natural gas business strategy in indonesia through scenario planning , a case of pt. Pertamina gas - Tri Sukma Tarigan, Devina; Arif Sumirat, Erman (The Indonesian Journal of Business Administration, 2018)
Abstract. The LCT states optimal dividend policy of a firm is dependent on its LC stage. Mature firms have decline in investment opportunities, reduced cost in raising capital and growth rate enabling firm to pay dividends, unlike young firms. The purpose of this research is to create a search strategy to help investors choose optimal dividend-paying stock listed in LQ45 Index using 2 scorecards. Descriptive research uses secondary data from audited financial reports of 17 selected firms that qualified for 10 listings in LQ45 Index from the year 2013 to 2017. DPR scorecard use factor DPR and LCT scorecard use weighted factors: Liquidity (Cash/TA, weight 1), Profitability (ROA, weight 2), Life Cycle (RE/TA, weight 2), Maturity (RE/TE, weight 1) and Leverage (LTD/TA, weight -1) to show effect on firms’ decision to pay dividends and payout level. Scorecards’ sequenced 17 stocks from lowest (rank 1) to highest (rank 17) 5yr w.a. value. Rank 17 has highest propensity to pay dividends and payout level and vice versa for rank of one, thus ideal stock pick have high ranks in both scorecards. Result show UNVR ranking 14 in LCT and 17 in DPR scorecards as ideal stock pick. UNVR has highest propensity to pay dividends and maintained high payout level, thus optimal dividend paying stock for long-term investment. EIC analysis conducted shows UNVR risk to increased cost of raw material and debt level. UNVR should deleverage and eliminate non-performing segments to increase its stagnant profit. Firms’, investors and future researchers can apply scorecard on other indices using 10-yr analysis to compare sectoral trends and select dividend stock listed in other indices of IDX. Keywords: Dividend Policy, Dividend Stocks, IDX, Life Cycle Theory, LQ45 Index